ТАРИЙХ САБАҚЛАРЫНДА ТАРИЙХЫЙ ДЕРЕКЛЕРДЕН ПАЙДАЛАНЫЎ УСЫЛЛАРЫ - Баўетдинов, Р.А. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of issues of effective using of historical sources. There is an analysis of the methods of using historical sources. The author emphasizes the positive influence of historical sources in increasing the quality and outcome of the lesson.
Keywords: тарих; тарихий манбалар; моддий ва ёзма манбалар; манбашунослик; тарихий хотира; археологик топилмалар; саёҳат дарслари; музей экспонатлари